Diskursus Seputar Tafsir bi al-Ma’thur - Hidayati Hidayati (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2020)
This research shows that interpreting of Qur’an using the transmitted interpretation (tafsir bi al-ma'thur ) is the interpretation of the al-Qur'an which has the highest value because it is based on naqli and not on the personal thoughts of the mufassir. However, there are also some figures who reject tafsir bi al-ma'thur as the best interpretation, and consider tafsir bi al-ma'thur to be a barrier to the meaning of al-Qur'an and not relevant to be applied in this era. Judging from its development, tafsir bi al-ma'thur did experience a setback and did not develop as logic based interpretation (tafsir bi al-ra’yi) especially in Indonesia. However, with the coming of new ways of interpreting the Qur’an, the transmission based interpretation should not be neglected nor forgotten, this kind of interpretation should be noticed and considered, to prevent the interpretation of Qur’an which depends only on logic. In this research, the writer presents the discourse about tafsir bi al-ma'thur, including the problems of tafsir bi al-ma'thur among the scholars, as well as the development of this interpretation in Indonesia from the classical period to the modern period. The approach used is a socio-historical approach, with descriptive-analysis research.